Regional Extensions of the Water Bearing Formations in Central North Kordofan and West White Nile Area - MA, El Hadi; AE, Ibrahim; AA, Elmansour (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
This study was done to delineate the regional extensions of the water bearing formations in the area lies between Central North Kordofan and West White Nile States. Interpretation of 23 vertical electrical soundings (VES) correlated with 66 borehole’s data to construct geological sections; IPI2Win software was used for VES data ID interpretation. The study indicates that, the area involves three water bearing formations; those are upper, lower and deep aquifer. The upper and lower aquifers extend in Bara Basin and the western part of Kosti Basin, while the deep aquifer is confined only to Kosti Basin. The upper and lower aquifers are composed of similar rocks of coarse sands and gravels whereas the deep aquifer is mainly made up of medium sands. Contrary to the popular belief that the upper aquifer is southerly limited by latitude 13o 00’N, the lithological and hydro geological evidences from the borehole’s reports indicate that, the upper aquifer extends in the southern parts of the area, south Khor Abu Habil. Also the mode of occurrence, rock type, and hydraulic condition of the deep aquifer indicated that the aquifer is not a part of the lower aquifer. How to cite this article: El Hadi MA, Ibrahim AE, Elmansour AA. Regional Extensions of the Water Bearing Formations in Central North Kordofan and West White Nile Area. J Adv Res Geo Sci Rem Sens 2020; 7(1&2): 24-30.